What Makes Life Grievable? Discursive Distribution of Vulnerability in the Pandemic (Czech Journal of International Relations, 2020)
This article examines Judith Butler’s concepts of vulnerability and grievability in the context of the COVID-19 pandemic and biopower practices introduced in the name of the protection of the people. An analysis of the elite political discourse in Czechia, Germany, Great Britain, and Slovakia in the first three months of the pandemic explores how vulnerability was constructed and distributed among the respective populations. We identified two prevailing discursive frames – science and security. Within the first, vulnerability was constructed in terms of biological characteristics, rendering elderly, disabled, and chronically ill bodies as already lost and ungrievable. Within the security frame, Roma or migrant populations’ vulnerability to the virus has been discursively shifted into being seen as a threat, while vulnerability itself was recognized more as a feature of institutions or society. Thus, despite the claims that ‘we are all in this together’, the pandemic has exposed how our vulnerability and interdependency are embedded within existing social structures.
Keywords: COVID-19; vulnerability; precarity; grievability; pandemic politics